The volume of agricultural credit, influences the percentage share of agriculture in GDP - Santillán López, Luis Gerardo; Medrano Freire, Eva Leonor (Revista Universidad de Guayaquil, 2015)
When governments manage the welfare of their societies, they must effectively manage the resources they have, they do not always create the conditions necessary to prioritize the most suitable for the development of their countries’ public policies. This research allows us to demonstrate that one of the priorities of a government for public policy is the funding for the agricultural sector through credit. For the analysis we used an innovative methodology, called alpha- beta method, volume data take credit for crops applied from 2004 to 2012 in a specific geographical area. We apply a simple regression model, falsifying the theory, hypothesis testing using correlation coefficient in the analysis of the influence of the financial operations of agricultural credit for crops, the level of participation of agriculture in the gross domestic producto
Keywords: Agricultural sector; agricultural credit; Alpha - Beta method